Investigation of fracture causes of the titanium alloy drill pipe in ultra-short radius horizontal well drilling. (October 2022) - Liu, Qiang; Tong, Ke; Zhu, Guo-chuan; Tan, Yi; Zhang, Juantao; Xu, Xin; Li, Xiaojun; Song, Sheng-yin
Highlights: The vulnerabilities in inspection methods of the current titanium alloy drill pipe standards were found. There are many micro-cracks on the surface of titanium alloy drill pipes that cannot be detected according to the current standards. The drill pipe body had slight deformation at the beginning of the oblique section for ultra-short radius drilling process. Suggestions for improving the standard of titanium alloy drill pipe in such extreme ultra-short radius drilling condition were put forward. Abstract: Recently, the first titanium alloy drill pipe failure accident occurred during the drilling of an ultra-short radius horizontal well in China, physical and chemical analysis, microstructure observation, SEM, full-scale torsion tests and FEA were conducted. The results revealed that the physical and chemical properties of the failed drill pipe complied with the requirements of the related standards. There are many micro-cracks on the surface of titanium alloy drill pipes that cannot be detected according to the current standards, when the titanium alloy drill pipe was used under the ultra-short radius horizontal drilling condition, the pipe body had slight deformation and these micro-cracks rapidly expanded throughout the entire wall thickness, resulting in the fracture failure of the titanium alloy drill pipe during ultra-short radius drilling. Suggestions for improving the inspection and standard of titanium alloy drill pipe in such extreme ultra-short radius drilling condition were also put forward.